Transmedia storytelling in expanding audience’s engagement: a phenomenological study of Nussa Rara - Hasan bin Jali; Mawaidi; Lalu Habiburrahman (Lingua Technica: Journal of Digital Literary Studies, 2025)
Background: The evolution of digital storytelling has transformed audience engagement, particularly through the utilization of multiple media platforms. Objective: This study aims to explore how the Nussa Rara franchise has expanded its narrative universe across various platforms—YouTube, a feature film, interactive AR, and merchandise—to enhance audience experience and engagement. Method: Using a qualitative research approach, the study analyzed content and collected audience feedback through interviews and surveys. Results: Results indicate that each platform uniquely contributes to deepening the narrative experience, with YouTube providing accessibility, the film adding emotional depth, AR enhancing interactivity, and merchandise creating a tangible connection to the story. Implication: These findings underscore the effectiveness of integrated media strategies in building compelling transmedia narratives. Novelty: The findings contribute to scholarly discussions by illustrating how different media formats can be harmoniously integrated to enhance storytelling.